2021
DOI: 10.1126/sciadv.abg7291
|View full text |Cite
|
Sign up to set email alerts
|

Switchable immune modulator for tumor-specific activation of anticancer immunity

Abstract: Immune stimulatory antibodies and cytokines elicit potent antitumor immunity. However, the dose-limiting systemic toxicity greatly hinders their clinical applications. Here, we demonstrate a chemical approach, termed "switchable" immune modulator (Sw-IM), to limit the systemic exposure and therefore ameliorate their toxicities. Sw-IM is a biomacromolecular therapeutic reversibly masked by biocompatible polymers through chemical linkers that are responsive to tumor-specific stimuli, such as high reducing potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…Pronounced splenomegaly was noted for mice treated with siRab@aPDL1/PLTs, probably due to the massive expansion of CD8 + T cells that indicated marked immune response (Figures S22 and S23, Supporting Information). [ 21 ] Nonetheless, the spleens from mice treated with siRab@aPDL1/PLTs recovered to the normal size and weight of those from healthy mice on day 35 (tumors being surgically removed on day 7, Figure S23, Supporting Information). It thus demonstrated that the splenomegaly was transient and nonpathologic, and could be recovered.…”
Section: Resultsmentioning
confidence: 99%
“…Pronounced splenomegaly was noted for mice treated with siRab@aPDL1/PLTs, probably due to the massive expansion of CD8 + T cells that indicated marked immune response (Figures S22 and S23, Supporting Information). [ 21 ] Nonetheless, the spleens from mice treated with siRab@aPDL1/PLTs recovered to the normal size and weight of those from healthy mice on day 35 (tumors being surgically removed on day 7, Figure S23, Supporting Information). It thus demonstrated that the splenomegaly was transient and nonpathologic, and could be recovered.…”
Section: Resultsmentioning
confidence: 99%
“…305 For instance, Irvine's group took advantage of the specific physiological environment in the TME to transform hydrophilic polymers such as PEG into immunomodulatory proteins (such as anti-4-1BB agonistic antibody, and IL-15 cytokine) using responsive covalent linkers such as disulfide bonds and maleimides, to block biological activity and avoid toxicity to normal tissues by using switchable immune modulator (Sw-IM); the therapeutic effect on solid tumours was enhanced by adoptive T cell transfer (ACT). 306 The results showed that the use of “switch” IL-15 cytokine super agonist (Sw redox IL15) combined with ACT not only achieved a normal IL-15 anti-tumour effect of super agonists but also effectively avoided the activation and expansion of CD8 + T cells and NK cells in healthy tissues and irAEs. In B16F10 tumour-bearing-mice, the cytokine IL-15 is specifically stimulated and released.…”
Section: Nanogels For Immunomodulatory Therapeuticsmentioning
confidence: 99%
“…In the Pro-XTEN concept, the low immunogenic XTEN masks reduce systemic exposure by serving as spatial shields that can be removed by the intrinsically high protease activity in the tumor [ 51 ]. Beyond such a genetic engineering approach, biocompatible polymers were also used to enlarge the therapeutic window by limiting the systemic exposure of therapeutic candidates [ 95 ]. In the concept of switchable immune modulators (Sw-IM), biologics were reversibly blocked by biocompatible polymers via a tumor microenvironment responsive covalent chemical linker.…”
Section: Conditionally Activatable Immunotoxins For Improved Overall ...mentioning
confidence: 99%
“…In the concept of switchable immune modulators (Sw-IM), biologics were reversibly blocked by biocompatible polymers via a tumor microenvironment responsive covalent chemical linker. The redox-responsive and/or pH-responsive stimuli in the tumor microenvironment degrade the chemical linker to achieve selective activation [ 95 ]. Such a concept was validated with several immune-modulating antibodies against immune checkpoints like 4-1BB, PD-1 and CTLA-4 [ 95 ].…”
Section: Conditionally Activatable Immunotoxins For Improved Overall ...mentioning
confidence: 99%
See 1 more Smart Citation